Report proposed interior design for Nuh’s Ark Islamic (Montessori) School at Lot 54 - 58, Section 71, Jalan Bukit Tunku, 50480 Kuala Lumpur / Siti Hasniah Hassan - Hassan, Siti Hasniah (Faculty of Architecture, Planning and Surveying, 2004)
Overall, this project is proposed interior design for Nuh’s Ark Islamic ( Montessori ) School, which one of the Islamic Preschool in Shah Alam. The existing preschool is located at No. 1 Jalan Paladium Tiga, 7/33 C Section 7, 40000 Shah Alam, Selangor Darul Ehsan. The one of the objective is to design a space which have connection between interior space according to Islamic fundamental and children nowadays. By this Islamic Preschool project, all information found which appropriate were put in design of modern Islamic preschool. These are combination idea between the owner of Nuh’s Ark Islamic Montessori School and me to design a new space that holding the Islamic fundamental as a guide to a better preschool and students in the future. These are consistent with the main philosophy that is “educating young children is to lay a sound foundation for the development of a wholesome personality”. It also can be as a reference as for an Islamic preschool in that area in developing the young mind that follows the Islamic rules for a better future.